A T3SS Regulator Mutant HY9901 ΔaraC of Vibrio alginolyticus Decreased the Expression of HopPmaJ and Provided Protection to Danio rerio as a Live-Attenuated Vaccine - Wang, Junlin; Zeng, Fuyuan; Feng, Haiyun; Chen, Liangchuan; Zhang, Weijie; Xiao, Xing; Monaghan, Sean J.; Jian, Jichang; Pang, Huanying; Wang, Na (Frontiers in Marine Science, 2022)
Vibrio alginolyticus, a zoonotic bacterial pathogen, expresses a type III secretion system (T3SS) that is critical for pathogen virulence and disease development. In this study, the mutant HY9901 ΔaraC was obtained from the laboratory and its biological characteristics were analyzed. The swimming ability of ΔaraC decreased and exhibited a 2600 times reduction in virulence to zebrafish. However, ΔaraC showed no difference in growth and extracellular protease activity compared to wild-type. Biofilm forming ability was improved at 24 h, but no difference was observed at other time points. The results of drug sensitivity testing showed that compared with the wild strain, ΔaraC was sensitive to amikacin, tetracycline, neomycin, minocycline and gentamicin. The transcription levels of T3SS effector proteins HopPmaJ, VopS, VcrV, VopN were analyzed by qRT-PCR. The results showed that ΔaraC had significantly up-reulated the mRNA expression of VopS, VcrV, VopN, but significantly down-regulated the mRNA expression of HopPmaJ at each stage compared with HY9901. Western blotting and the β-galactosidase reporter gene experiment also showed that the deletion of araC gene significantly down-regulated the expression of HopPmaJ. Finally, the relative percent survival rate (RPS) of grouper inoculated by intramuscular (IM) injection of HY9901 ΔaraC was 61.3% after being challenged with HY9901. Real-time qPCR analysis showed that vaccination of HY9901 ΔaraC could enhance the expression of immune-related genes, including GATA-1, IL6, IgM, IL-1β, LYZ in liver and spleen, indicating that ΔaraC applied as an attenuated live vaccine effectively induced an immune response in the zebrafish. This study provides evidence for the subsequent development of an effective live attenuated V. alginolyticus vaccine.